1439 A Change in The Use of Post-Operative Drains in Total Knee Arthroplasty (TKA). (12th October 2021) - Erdman, P; Ali, R; Bhattacharya, R
Abstract: Aim: Closed suction drains (CSD) are routinely used to reduce the risk of haematoma formation and wound infections in TKA. Our study aims to determine if the use of drains has any impact on estimated blood loss, transfusion rates and length of stay in hospital. Method: Elective TKA cases performed under a single consultant between February 2018-March 2020 were identified. Electronic medical records were reviewed, and data collected on relevant variables. Estimated blood loss was calculated using Ward's formula. Mann-Whitney U test was applied to assess for statistical significance. Results: A total of 86 elective TKA cases were included in the study. In 41 cases patients had a CSD insitu post-operatively (group 1), in the other 45 cases a drain was not used (group 2). Both groups had similar distributions of age, BMI, and sex. We found no statistically significant differences in mean change (+/-SD) in haemoglobin post-operatively between group 1 (21.3 (+/- 9.4)) and group 2 (19 (+/- 10)), (p = 0.34). Mean estimated blood loss was 915mls (+/-365) for group 1 and 871mls (+/-455) for group 2, (p = 0.45). Group 1 had a higher rate of transfusion (4.8% vs 2.2%); however, this was not statistically significant (p = 0.51). After accounting for unrelated medical complications or social barriers to discharge, the length of hospital stay was 4.7 (+/- 2.27) and 4.9 (+/- 3.14) for group 1 and 2 respectively, (p = 0.84). There were no reported cases of wound infection in both groups. Conclusions: We found the use of drains in TKA confers no benefits in the outcomes evaluated.